Teacher efficacy and attributes on the implementation of tiered instructional frameworks - Janet Alys Nichols; William Dee Nichols; William H. Rupley (Institute of Advanced Engineering and Science, 2020)
United States federal mandates and reforms to address the needs of at-risk students have resulted in many states being required to implement evidence-based practices (EBP) and tiered systems of support (TSS). We examined the relationships between successful implementation of EBP and tiered frameworks, specifically Positive Behavior Interventions and Support (PBIS) and the constructs of teacher self-efficacy, collective efficacy, and teacher attributions. Data were collected using the School-wide Evaluation Tool (SET), Teacher Self-Efficacy Scale (TSES), the Collective Efficacy Scale (CES), and Teachers’ Attributions for Student Behavior Measure (TASBM). Significant correlations were found between PBIS implementation level and 1) Instructional Strategies subscale of the TSES; 2) Collective Efficacy Scale and both of its subscales; and 3) TASBM and its Stable and Blame subscales. Significant differences in mean ratings were found between high implementing schools and low implementing schools on the Instructional Strategies subscale of the TSES, on the CES, and both of its subscale. Results showed a decrease in mean ratings on the Blame subscale of the TASBM in schools that had higher implementation scores on the SET.